Increased expression of cytochrome P450 2E1 in nonalcoholic fatty liver disease: Mechanisms and pathophysiological role - Aubert, J.; Begriche, K.; Knockaert, L.; Robin, M.A.; Fromenty, B. (Clinics and research in hepatology and gastroenterology, 2011)
Due to the worldwide surge in obesity and type 2 diabetes, the increased incidence of nonalcoholic fatty liver disease (NAFLD) is a major concern for the public health. Indeed, NAFLD encompasses a large spectrum of conditions ranging from fatty liver to nonalcoholic steatohepatitis (NASH), which can progress to cirrhosis in some patients. A better understanding of the mechanisms involved in fatty liver and its progression into NASH is important in order to develop efficient drugs able to alleviate these liver diseases. Although numerous investigations pointed to reactive oxygen species (ROS) as key players in the progression of fatty liver to NASH, their exact source is still uncertain. Besides the mitochondrial respiratory chain, cytochrome P450 2E1 (CYP2E1) has recently emerged as another potentially important cause of ROS overproduction. Indeed, higher hepatic CYP2E1 expression and activity have been frequently observed in the context of obesity and NAFLD. It is currently unknown why CYP2E1 is enhanced in these dysmetabolic diseases, although increased hepatic levels of fatty acids and insulin resistance might play a role. Nonetheless, higher hepatic CYP2E1 could play a significant role in the pathophysiology of NASH by inducing lipid peroxidation and oxidative damage of key cellular components. Moreover, CYP2E1-mediated overproduction of ROS could promote hepatic insulin resistance, which can further aggravate fatty liver. Since a significant amount of CYP2E1 can be located within liver mitochondria, higher levels of CYP2E1 in NAFLD could also have detrimental effects on mitochondrial function. Finally, increased CYP2E1 activity during NAFLD could enhance the susceptibility of some patients to the hepatotoxicity of different xenobiotics through the CYP2E1-mediated generation of harmful reactive metabolites.